Revisiting the Link between Trade, Growth and Inequality : Lessons for Latin America and the Caribbean - Beaton, Kimberly (IMF Working Papers; Working Paper, 2017)
We revisit the relationship between international trade, economic growth and inequality with a focus on Latin America and the Caribbean. The paper combines two approaches: First, we employ a cross-country panel framework to analyze the macroeconomic effects of international trade on economic growth and inequality considering the strength of trade connections as well as characteristics of countries' export markets and products. Second, we consider event studies of past episodes of trade liberalization to extract general lessons on the impact of trade liberalization on economic growth and its structure and inequality. Both approaches consistently point to two broad messages: First, trade openness and connectivity to the center of the trade network has substantial macroeconomic benefits. Second, we do not find a statistically significant or economically sizable direct impact of trade on overall income inequality.